Four new species of the genus Paraustrorhynchus (Rhabdocoela: Kalyptorhynchia: Polycystididae) - Lin, Yitao; Reygel, Patrick; Feng, Weitao; Chen, Jiajia; Tessens, Bart; van Steenkiste, Niels W. L.; Schockaert, Ernest R.; Artois, Tom J.; Wang, Antai (Zootaxa, 2019)
Four new species of Paraustrorhynchus (Rhabdocoela: Kalyptorhynchia: Polycystididae) are described: two from Southern China (P. shenda n. sp., P. sinensis n. sp.), one from New Caledonia (P. isoldeae n. sp.), and one from India (P. smeetsae n. sp.). All four species show a typical dark blue dorsal pigmentation pattern, which is unique to the genus. This pigment forms a broad longitudinal line in P. shenda n. sp. and P. sinensis n. sp., shows an additional transverse band at the level of the pharynx in P. smeetsae n. sp. and forms a Y-shaped pattern in P. isoldeae n. sp. The four species can also be distinguished from each other and their congeners by the detailed morphology of the hard parts of the male system, which in all cases consists of an L-shaped (P. shenda n. sp., P. isoldeae n. sp) or slightly-curved (P. smeetsae n. sp., P. sinensis n. sp.) prostate stylet type II and a prostate stylet type III, which consists of three plates: a basal plate from which two longer plates depart, each with a distal serrated rim. A phylogenetic analysis based on 18S and 28S-rDNA data indicates that Paraustrorhynchus is a monophyletic taxon within Polycystidinae, with Alcha evelinae as the sister group.